RANKING FACTORS AFFECTING PUBLIC TRANSPORT MODE CHOICE OF COMMUTERS IN AN URBAN CITY USING THE ANALYTIC HIERARCHY PROCESS: THE CASE OF SURABAYA, INDONESIA - Corina Irish Yuswandhika; Ainun Nafisah (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to identify and rank the factors influencing commuters’ public transport choices and to evaluate their preferences for different modes of transport. A quantitative survey was conducted with 63 provided consistent responses based on the Analytic Hierarchy Process (AHP). Four decision criteria were assessed: cost, safety, time efficiency, and comfort. Alongside five public transport alternatives: city bus, intercity bus, feeder bus, commuter train, and public minivan. Results revealed that time efficiency is the most influential factor shaping commuters’ choices, followed by safety, cost, and comfort. In terms of mode preference, the commuter train ranked highest, reflecting its reliability and punctuality, while public minivan ranked lowest, primarily due to declining service quality and competition from ride-hailing services. These findings highlight the need to prioritize service reliability of time efficiency, safety, and affordability to increase public transport usage in Surabaya.